2019
DOI: 10.1177/0258042x19890245
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identity Impact on Consumers’ Ethnocentric Tendencies: The Moderating Role of Acculturation and Materialism

Abstract: In the era of globalization and technological advancements, ethnic identity (EID) is creating both opportunities as well as challenges for domestic and international marketers in formulating suitable marketing and branding strategies. This study attempts to investigate the role of EID in shaping consumers’ ethnocentric tendencies (CET). By analyzing data obtained from 385 surveys completed by Indian consumers, the study assessed the association of EID dimensions and consumer ethnocentrism. The findings showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Third, the results indicated that consumers who value social acceptance and adhere social norms are more likely to be inspired and engaged towards prestige quotient of a brand. As people with collectivist orientation exhibits such type of uniqueness (Das & Mukherjee, 2020), it can be argued that masstige consumption could be a culture‐driven phenomenon. Hence, future research could explore the role of various cultural constructs (e.g., cosmopolitanism, individualism, collectivism etc.)…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Third, the results indicated that consumers who value social acceptance and adhere social norms are more likely to be inspired and engaged towards prestige quotient of a brand. As people with collectivist orientation exhibits such type of uniqueness (Das & Mukherjee, 2020), it can be argued that masstige consumption could be a culture‐driven phenomenon. Hence, future research could explore the role of various cultural constructs (e.g., cosmopolitanism, individualism, collectivism etc.)…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Finally, existing research shows that continental nature of migration into North America, Europe and some parts of Asia plays a vital role in shaping the acculturation of the migrants (Redfield, Linton & Herskovits, 1935, Das, 2019Gindelsky, 2017;Beals, 1951;Kessler & Milligan, 2019;Thompson, 1948;Ahmmad & Adkins, 2019;Liu, 2017;Kodja & Lebedeva, 2018;Groenewold & de Valk;Kodja & Ryabichenko, 2019). The common trend is that continental migrants reserve little or no option in acclimatising in the new environment.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The association of 6.1) altruistic values and 6. Concern for the environment requires a caring and sacrificial mindset which is perceived to be more prevalent in feminine cultures than in masculine (Das and Mukherjee, 2020). Accordingly, concern and care for others in feminine societies are expected to be reflected through various activities, including green consumption.…”
Section: Power Distancementioning
confidence: 99%